Решите уравнение 6 x 2-4x 6 x 2-4x-1 42

2*9^x^2-4x+1+42*6^x^2-4x-15*4^x^2-4x+1=0 18^х^2-4х+1+252^х^2-4х-60^х^2-4х+1=0 210^х^2-12х+2=0 делим всё на 2 получается 105^х^2-6х+1=0. 6^(x^2-4x) + 6^(x^2-4x-1) = 42 6* 6^(x^2-4x) + 6^(x^2-4x)=42*6 6^(x^2-4x)(6+1)=42*6 6^(x^2-4x)*7=42*6 6^(x^2-4x)=6^2 x^2-4x=2 x^2-4x-2=0. D=16+4*2=24. Здравствуйте! 6X+1=-4X 6х+4х=-1 10х=-1 х=-1:10 х=-0,1 2). 2+3X=-7X-5 7х+3х=-5-3 10х=-8 х=-0,8 3). 7+5(-9X+7)=-3 7-45x+35=-3 42-45x=-3 -45х=-3-42.

Нажми, чтобы увидеть ответ на свой вопрос ✍ : 6^(x^2-4x)+6^(x^2-4x-1)=42. РЕШЕНИЕ: а) 6x2–4x+6x2–4x–1=42 6x2–4x+(1/6)·6x2–4x=42. Замена: 6x2–4x=t ⇒ t+(1/6)t=42 (7/6)t=42 t=36=62 6x2–4x=62 x2–4x=2 x2–4x–2=0. Ответы и объяснения. Mydrый. Лучший Ответ! 6^(x²-4x-1)*(6+1)=42 6^(x²-4x-1)=6 x²-4x-1=1 x²-4x-2=0.